Marine heatwave associated Betanodavirus outbreak in wild groupers of the Azores - Gomes, Inês; Novoa-Pabon, Ana; Abbadi, Miriam; Pretto, Tobia; Rosa, Joana; Silva, Luís; Torres, Paulo; Marsella, Andrea; Afonso, Pedro; Toffan, Anna (Frontiers in Marine Science, 2025)
This study reports the first viral nervous necrosis (VNN) outbreak in wild dusky grouper (Epinephelus marginatus) in the North Atlantic, and the first detection of the virus in island grouper (Mycteroperca fusca). Most affected fish displayed typical VNN clinical signs and lesions, and laboratory analyses confirmed the virus as the primary cause of mortality. The majority of the diseased individuals were large adults, underscoring the risk to stock sustainability and conservation of this vulnerable and iconic species. Viral sequences were highly homogeneous (>99% nucleotide similarity), suggesting a single, recent introduction. The outbreak coincided with a severe marine heatwave affecting the Azorean Archipelago in the summer of 2024, during which sea surface temperatures exceeded 25 °C, the optimal range for the RGNNV genotype replication. The absence of fatalities in the eastern islands may be due to several factors, including heterogeneous introduction pathways, oceanographic differences, and lower grouper densities. This event highlights the vulnerability of long-lived, site-attached species to emerging pathogens, particularly under climate-driven stress. Effective management requires coordinated regional responses, ecosystem monitoring and early detection systems to prevent further spread and safeguard wild grouper populations.